2017
DOI: 10.1002/bdr2.1164
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Zika descriptive epidemiology of microcephaly in Texas, 2008–2012

Abstract: We found that risk patterns for microcephaly varied across case groupings. Risk factors included maternal race/ethnicity, age, and smoking during pregnancy. Among severe unexplained cases, notable positive associations were seen among mothers who were non-Hispanic Black or less educated, while inverse associations were noted for obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(53 reference statements)
1
6
1
Order By: Relevance
“…The prevalence of 4.0 cases of congenital microcephaly per 10,000 live births observed in this study is lower than rates of 5.5, 8.7, and 14.7 cases per 10,000 births reported by three recent studies, respectively (Cragan et al, ; Hansen et al, ; Hoyt et al, ). The lower prevalence in our study may have occurred, because we only ascertained cases diagnosed in the neonatal period, whereas the other three studies included diagnoses made at the time of birth and during the first year of life or later.…”
Section: Discussioncontrasting
confidence: 73%
“…The prevalence of 4.0 cases of congenital microcephaly per 10,000 live births observed in this study is lower than rates of 5.5, 8.7, and 14.7 cases per 10,000 births reported by three recent studies, respectively (Cragan et al, ; Hansen et al, ; Hoyt et al, ). The lower prevalence in our study may have occurred, because we only ascertained cases diagnosed in the neonatal period, whereas the other three studies included diagnoses made at the time of birth and during the first year of life or later.…”
Section: Discussioncontrasting
confidence: 73%
“…Furthermore, in a type 2 diabetes mouse model, lower expression of cell adhesion molecules reduced leukocytes recruitment, resulting in a failure to clear WNV infection from the brain and leading to increased inflammatory molecule levels, which increases neuronal cell death and mortality in mice with type 2 diabetes [ 48 , 49 ]. Some studies also reported that the children of mothers who are diabetic (pre-pregnancy or gestational) are at higher risk for both explained and unexplained microcephaly during ZIKV infection [ 50 , 51 ]. Taken together, several members of Flaviviridae including DENV appear to be associated with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States and Europe, the reported prevalence of microcephaly ranges from 2.0 to 14.7 per 10,000 live births. [9][10][11] However, data from low resource settings (LRSs) suggests that the incidence rates of microcephaly may be substantially higher. 12,13 In the rural southwest region of Guatemala, we documented a very high prevalence of microcephaly (1216 per 10,000 live births) in April of 2015, 12 prior to the arrival of the Zika epidemic in late 2015.…”
Section: Introductionmentioning
confidence: 99%